2014
DOI: 10.1152/jn.00308.2014
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor training alters the behavior of flexor reflexes during walking in human spinal cord injury

Abstract: In humans, a chronic spinal cord injury (SCI) impairs the excitability of pathways mediating early flexor reflexes and increases the excitability of late, long-lasting flexor reflexes. We hypothesized that in individuals with SCI, locomotor training will alter the behavior of these spinally mediated reflexes. Nine individuals who had either chronic clinically motor complete or incomplete SCI received an average of 44 locomotor training sessions. Flexor reflexes, elicited via sural nerve stimulation of the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…We have recently shown that locomotor training changes the behavior of short-and long-latency flexion reflexes, reestablishes a physiologic soleus H-reflex phasedependent modulation, increases presynaptic inhibitory control of soleus motoneurons, modifies excitability properties of so- percentage of change of the conditioned H reflex during seated from all subjects after training, reflecting the magnitude of reciprocal and nonreciprocal inhibition, is plotted against the years postinjury. leus motoneurons, changes cocontraction levels between knee and ankle antagonistic muscles, and promotes interlimb and intralimb EMG coordination in the same people with SCI tested here (Knikou 2013;Knikou and Mummidisetty 2014;Smith et al 2014Smith et al , 2015. Because the modulation of soleus H-reflex inhibition by presynaptic inhibition after training was completely different from the soleus H-reflex postsynaptic inhibition in the same patients tested in this study, the changes observed after locomotor training can be attributed to changes in the intrinsic properties, function, and synaptic inputs of Ia and Ib inhibitory interneurons.…”
Section: Possible Mechanisms For Plasticity Of Postsynaptic Inhibitiomentioning
confidence: 76%
See 2 more Smart Citations
“…We have recently shown that locomotor training changes the behavior of short-and long-latency flexion reflexes, reestablishes a physiologic soleus H-reflex phasedependent modulation, increases presynaptic inhibitory control of soleus motoneurons, modifies excitability properties of so- percentage of change of the conditioned H reflex during seated from all subjects after training, reflecting the magnitude of reciprocal and nonreciprocal inhibition, is plotted against the years postinjury. leus motoneurons, changes cocontraction levels between knee and ankle antagonistic muscles, and promotes interlimb and intralimb EMG coordination in the same people with SCI tested here (Knikou 2013;Knikou and Mummidisetty 2014;Smith et al 2014Smith et al , 2015. Because the modulation of soleus H-reflex inhibition by presynaptic inhibition after training was completely different from the soleus H-reflex postsynaptic inhibition in the same patients tested in this study, the changes observed after locomotor training can be attributed to changes in the intrinsic properties, function, and synaptic inputs of Ia and Ib inhibitory interneurons.…”
Section: Possible Mechanisms For Plasticity Of Postsynaptic Inhibitiomentioning
confidence: 76%
“…Subjects' consent was obtained according to the Declaration of Helsinki. Subjects also participated in previous studies (Knikou 2013;Knikou and Mummidisetty 2014;Smith et al 2014Smith et al , 2015 and are identified here with the same code. Subjects R09 and R20 did not participate in the Ib inhibition experiment.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Persons with SCI who participate in locomotor training demonstrate more typical modulation of spinal reflex excitability after training compared with their pre-training levels. [72][73][74][75] The importance of changes in reflexes should be considered in conjunction with observable improvements in overground walking; for example, improvement in overground walking speed is correlated with reduction in clonus and H-reflex magnitude. 73,76 The observation that reflex modulation can change in the absence of measurable change in the walking outcome, 77 however, suggests either that the reflex modulation is an epiphenomenon unrelated to walking performance or that the walking measures are not sufficiently sensitive to the changes in gait that accompany improved reflex modulation.…”
Section: Training-related Modulation Of Spinal Circuitsmentioning
confidence: 99%
“…However, existing evidence suggests that transmission of nociceptive signals results in a multitude of unfavorable effects over the locomotor circuitry [212,213] that has an otherwise high capacity for retraining, given the appropriate proprioceptive feedback [153,[214][215][216].…”
Section: Discussionmentioning
confidence: 99%